Investigation of the attitudes of medical/nursing staff and patients towards nurse prescribing - Ioanna Lourantaki; Korina Katsaliaki (Ene, 2018)
Introduction: Prescribing by specialized nurses is an expanded role, already successfully performed in many countries. Purpose: Recording preferences and comparing the views of medical staff, nurses and patients, towards the prescribing of specialized higher education nurses. Methodology: This is a quantitative study, conducted in two public hospitals, including 200 nurses, 200 medical staff and 200 patients. The designed questionnaire for data collection included demographic data of patients, medical staff and nurses and questions for nurses' prescription. Statistical analysis was performed with SPSS statistical package 20. Results: One hundred forty-eight questionnaires were collected from patients 107 from medical staff and 183 from nurses. The results showed that once becoming legal in our country patients (38%), to a greater percentage, would prefer qualified nurses to prescribe commonly used drugs, while medical staff (42.2%) and nurses (45.4%) would prefer nurses not to prescribe new drugs but to be able to change the time or the dosage of a medication. Also the patients (44.9%), to a greater percentage, would prefer their nurses to prescribe medical supplies and diagnostic exams and refer patients to other health professionals, while the other two groups showed a positive preference only to the prescription of health materials (56.1% physicians and 45.9% nurses). Regarding the question of whether the prescribing of higher education nurses could contribute to faster and more efficient patient access to medicines, the majority of patients (51.4%) and nurses (47.6%) are in favor, but the medical staffs disagree. Conclusions: Patients' attitudes were more positive in all aspects of prescribing compared to those of nurses and medical staff. The redefinition of the nurse's role can help maintain a satisfactory level of healthcare services with fewer financial resources without being considered "quasi-doctors", but as nurses with extended scope of practice who contribute to the healthcare system in different ways.